(untitled) (Journal of Scientific Research, 2015)
The main objective of this study is to determine the Gross alpha and gross beta radioactivity in environmental sample. Thirty samples of soil, water and vegetable were randomly collected from the different locations of Bheramara and Ishwardi near the proposed Rooppur Nuclear Power Plant area, Kushtia and Pabna, Bangladesh. The Gross Alpha activity under investigation ranges from 1.13 to 5.66 Bq kg-1 with an average of 2.78±0.16 Bq kg-1 for soil sample, 0.45 to 1.36 mBq L-1 with an average of 0.91± 0.18 mBq L-1 for water sample, and 0.23 to 1.81 Bq kg-1 with an average of 1.0 ±0.11 Bq kg-1 for vegetable sample. The Gross Beta activity under investigation ranges from 30.74 to 132 Bq kg-1 with an average of 71.85±1.99 Bq kg-1 for soil sample, 61.49 to 279 mBq L-1 with an average of 175 ±4.02 mBq L-1 for water sample, and 305 to 1676 Bq kg-1 with an average of 930 ±3.27 Bq kg-1 for vegetable sample. This study will help to prepare baseline data for gross alpha and gross beta radioactivity in environmental sample which will be used as finger print for the comparison of radioactivity level.